The Effect of Company Size, Leverage, and GCG on the Financial Performance of the Hospitality Industry Sector - Yudhanto, Wildan; Suroso, Agus; Rabiatul Adawiyah, Wiwiek (Research Horizon, 2025)
The hospitality industry plays a significant role in regional economic development, yet its financial performance is often influenced by various internal factors. This study aims to empirically examine the effect of company size, leverage, and Good Corporate Governance (GCG) on the financial performance of hospitality businesses. Employing a mixed-methods approach, the research collected data through purposive sampling, resulting in a total of 117 industry respondents. Quantitative data were analyzed using multiple linear regression, while qualitative insights were gathered to capture perceptions and experiences of industry practitioners involved in the study. The findings indicate that company size, leverage, and GCG significantly affect financial performance. By integrating quantitative and qualitative methods, this study offers a more comprehensive understanding of the factors shaping financial outcomes. Furthermore, this research contributes new evidence by specifically addressing the role of GCG, company size, and leverage in hospitality-sector firms, providing valuable implications for both scholars and industry stakeholders.